Do they really use more tag questions? - Muhammed Shahriar Haque; Wong, Bee Eng (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2003)
Tag questions are a feature of what Lakoff (1975) calls "women's language", and women by using them more than men project themselves as weak and uncertain. However, studies show inconsistent findings. This paper presents the findings of a study that examined whether the use of tag questions in the academic context might be more inclined to members of one gender. If so, what forms of tag questions are most frequently used and what are their functions? Furthermore, it is also important for us to realize the extent to which the speaker feels the use of tag questions affect her or his confidence level. The findings of this study show that the common myths of archetypal stereotypes regarding the use of tag questions and women, and the relationship between the use of tag questions and low confidence level may be unfounded